2019
DOI: 10.1111/insr.12328
|View full text |Cite
|
Sign up to set email alerts
|

Mixture of Truthful–Untruthful Responses in Public Surveys

Abstract: Summary When sensitive issues are surveyed, collecting truthful data and obtaining reliable estimates of population parameters is a persistent problem in many fields of applied research mostly in sociological, economic, demographic, ecological and medical studies. In this context, and moving from the so‐called negative survey, we consider the problem of estimating the proportion of population units belonging to the categories of a sensitive variable when collected data are affected by measurement errors produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The GSS "Sensitive Data Files" identify the location of each respondent by county: and it has incorporated methods to overcome bias from framing effects and subject nonresponses (Sterrett et al 2017). It is also regularly reviewed for potential sources of bias by researchers from a variety of disciplines on behalf of the NSF (Rasinski et al 1999;Christofides and Perri 2019). Using consistency across administrations to the same respondents spanning the period 2006-2014 and objective comparison data, Hout and Hastings (2016) found that the reliability of responses to more than 50% of the core questions in the GSS was greater than 70%.…”
Section: Data and Summary Statisticsmentioning
confidence: 99%
“…The GSS "Sensitive Data Files" identify the location of each respondent by county: and it has incorporated methods to overcome bias from framing effects and subject nonresponses (Sterrett et al 2017). It is also regularly reviewed for potential sources of bias by researchers from a variety of disciplines on behalf of the NSF (Rasinski et al 1999;Christofides and Perri 2019). Using consistency across administrations to the same respondents spanning the period 2006-2014 and objective comparison data, Hout and Hastings (2016) found that the reliability of responses to more than 50% of the core questions in the GSS was greater than 70%.…”
Section: Data and Summary Statisticsmentioning
confidence: 99%